US population qualifying for aspirin use for primary prevention of cardiovascular disease - Athena L. Huang; Ann Marie Navar; Colby Ayers; Anand Rohatgi; Erin D. Michos; Salim S. Virani; Parag Joshi; Eric D. Peterson; Amit Khera (Elsevier, 2024)
Objective: Aspirin has been used for primary prevention of atherosclerotic cardiovascular disease (ASCVD) for decades, but this indication has become controversial with recent trial data. The 2022 US Preventive Services Task Force (USPSTF) provided a recommendation to consider aspirin use for primary prevention in adults 40-59 years with a 10-year ASCVD risk ≥10 % and not at increased risk of bleeding, yet population estimates for the impact of this recommendation are unknown. The objective of this study is to determine the prevalence and demographics of the US population who meet eligibility criteria for aspirin under the new 2022 USPSTF guidelines. Methods: This is a serial cross-sectional study using data from the 2011-March 2020 National Health and Nutrition Examination Survey (NHANES) database. Individuals aged 40-59 years without a self-reported history of ASCVD were included. 10-year estimated ASCVD risk ≥10 % as calculated by the Pooled Cohort Equations (PCE) and increased bleeding risk determined using variables adapted from USPSTF guidelines were further applied as inclusion and exclusion criteria, respectively. The weighted frequencies of US adults aged 40-59 years qualifying for primary prevention aspirin, subgrouped by gender, age, and race/ethnicity, were calculated. Results: Among 72,840,734 US individuals aged 40-59 years, 7.2 million (10 %) are eligible for consideration of primary prevention aspirin by PCE criteria. Of these, approximately 30 % would be potentially excluded based on increased bleeding risks, resulting in a net eligible cohort of 5 million. This represents 7 % of US adults aged 40-59 years and only 2.6 % of adults ≥18 years. Men, age 50-59 years, and Black race have higher proportions meeting aspirin use eligibility. Conclusions: The overall prevalence of US individuals who qualify for aspirin for primary prevention under the 2022 USPSTF guidelines is modest, with larger proportional eligibility among men, older age, and Black individuals.